USING GRAMMAR TRANSLATION METHOD TO IMPROVE STUDENT'S COMPREHENSION AT SMP SWASTA PENGHARAPAN MEDAN - Tarigan, Sri Ninta; Siregar, Tiarnita Maria Sarjani; Barus, Luz Oktalia; Sigalingging, Mesrida (ELT (English Language Teaching Prima Journal), 2024)
This research was conducted to describe the process of increasing students' understanding of comparative degrees through the Grammar Translation Method and to find out whether the grammar-translation method can improve students' understanding of comparative degrees among Medan Pengharapan Private Middle School students. Class I and II students of Medan Pengharapan Private Middle School were the research subjects. Tests and observations are data collection tools. Students are taught using qualitative and quantitative approaches, or classroom action research. Based on this research, it can be concluded that students already understand when taking tests. This was proven when working on the first cycle: 28 students did not understand (below average) the degree of comparison, and after being given the first treatment, this increased to 12 students who understood it but did not understand comparative degrees. After being given the second treatment, only 10 students did not understand comparative degrees.